2023
DOI: 10.1111/jfd.13814
|View full text |Cite
|
Sign up to set email alerts
|

First identification and histopathological analysis of Lactococcus garvieae infection in whiteleg shrimp, Penaeus vannamei cultured in low salinity water

Abstract: The isolation and characterization of bacterial species Lactococcus garvieae, previously unreported in whiteleg shrimp, Penaeus vannamei, has now been identified in the species. The pathogen was recovered from an affected shrimp farm in southern Taiwan. Bacterial characterization first identified the isolate as Gram‐positive cocci, and biochemical profiles demonstrated that the causative agent of mortality was 97% L. garvieae. The bacterial cell DNA resulted in amplification of 1522 bp with 99.6% confirmation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In aquaculture, L. garvieae is an important pathogen that has been reported to cause severe infections in aquatic organisms, such as fish and shrimp. 48,49 L. garvieae also causes septicemia and endocarditis in humans. 50 It can also effectively evade host immune system monitoring and attack by producing polysaccharide pods, 51,52 which can impact immune recognition of the surface of the bacteria, making it difficult for immune cells to recognize and attack them.…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, L. garvieae is an important pathogen that has been reported to cause severe infections in aquatic organisms, such as fish and shrimp. 48,49 L. garvieae also causes septicemia and endocarditis in humans. 50 It can also effectively evade host immune system monitoring and attack by producing polysaccharide pods, 51,52 which can impact immune recognition of the surface of the bacteria, making it difficult for immune cells to recognize and attack them.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the genetics and regulation of capsular gene clusters in L. garvieae is crucial for developing effective disease prevention and treatment strategies (Shi et al, 2019). Interestingly, recent studies have suggested the possibility of multiple types of capsules in L. garvieae, such as the hyaluronic acid capsule, observed in L. garvieae isolated in whiteleg shrimp (Penaeus vannamei) and in cobia (Ballantyne et al, 2023;Rao et al, 2021). So, a thick capsule like structure observed in our In this study, PFGE and phylogenetic analyses were conducted to determine the genotypes of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…As climate change affects salinity patterns globally, understanding its impact on shrimp is essential for developing adaptive feeding strategies. Studies have shown that water salinity and dietary protein content significantly affect the growth performance of L. vannamei juveniles, with better performance observed at higher salinity and protein levels (Bardera et al, 2019; Rahi et al 2021; Pinho and Emerenciano, 2021; Ballantyne et al, 2023;). While the long-term impacts of salinity on shrimp have been explored, the immediate effects on feeding behaviour and how it interacts with environmental conditions remain under-studied.…”
Section: Introductionmentioning
confidence: 99%